Improving Students' Conceptual Understanding in Science Learning Using Image-Based Learning Methods at MI Rohmatul Ulum - Simpati, Hasis; Pentiani, Anris (MANDAILING GLOBAL EDUKASIA, 2025)
Action Research of Class IV MI Rohmatul Ulum around September to December 2021. The results of learning Natural Sciences of class IV MI ROHMATUL ULUM from several tests are still very low. From two tests, the average class score is still below the KKM, which is 75. The highest score is 70 while the lowest score is 50. In the second daily test, the highest score is 80 and the lowest score is 50. The average of the two daily tests is 67. The purpose of this study is to improve learning outcomes in classifying animals based on their food types in Natural Sciences learning for class IV students of MI Rohmatul Ulum, Sokobanah District, Sampang Regency, 2021/2022 Academic Year through the empowerment of student worksheets. The research was conducted at MI Rohmatul Ulum, Sokobanah District, Sampang Regency. The research period was from November to December 2021. The form of this research is Classroom Action Research. The actions taken consist of two actions in two cycles. Each cycle consists of four stages, namely planning, acting, observing and reflecting. The class studied was grade IV students of MI Rohmatul Ulum Sokobanah with a total of 15 students. After the first cycle was carried out, namely the teacher carried out direct learning practices, the results obtained in cycle 1 were that the average class value increased to 75. In cycle 2, the average value was 86. So from the initial condition to the final condition, there was an increase in learning outcomes from an average of 67 to 86. From the results of the action research carried out through two cycles, a very significant increase was obtained so that it can be concluded that with the empowerment of Student Worksheets.